EFFECTS OF CRUDE OIL THEFT ON INTERNAL SECURITY OF DELTA STATE - IKENNA GODWIN IKONNE (International Studies Journal)
This study examines how economic marginalization and weak governance fuel criminal activities, leading to violent confrontations between security forces and oil thieves, using the Frustration-Aggression Theory. Crude oil theft in Delta State poses significant threats to internal security, contributing to economic losses, environmental degradation, and increased violence. This study employs a mixed-methods approach, combining quantitative surveys with qualitative interviews among local communities, security personnel, and government officials. Findings indicate that oil theft is driven by unemployment, inadequate government intervention, and the complicity of local elites. Data analysis reveals that areas with high crude oil theft incidents experience increased militia activities, arms proliferation, and organized crime. Qualitative insights highlight the perceived injustice among local youth, who view oil theft as a means of economic survival. Security agencies struggle with inadequate resources and corruption, exacerbating the crisis. Strengthening security frameworks through enhanced intelligence sharing and community policing is recommended to curb oil-related crimes. Additionally, economic empowerment programmes targeting youth in affected areas in Delta State can reduce incentives for criminal participation. This study contributes to the literature by integrating the security and economic dimensions of crude oil theft, unlike previous studies that focused primarily on economic losses. It provides new empirical insights from mixed-methods data, bridging the gap between structural causes and security responses. The findings offer a holistic policy direction, emphasizing both punitive and preventive measures.